Covalent and noncovalent hybrids of di-amino porphyrin functionalized graphene oxide and their interaction with gold nanoparticles - Andrade, Suzana M. (2022)
Porphyrin functionalization of graphene oxide (GO) influenced the plasmonic effect of gold nanoparticles (AuNP). The former was achieved by modification of GO with 5,10-bis(4-aminophenyl)-15,20-diphenylpor-phyrin, P(NH2)2,adj, by noncovalent interactions as well as by covalent association, following standard chemis-try. The success of the chemical functionalization of GO with P(NH2)2,adj, was confirmed by FTIR. Steady-state and time-resolved fluorescence showed a strong fluorescence quenching of porphyrin in the presence of GO, indicative of a photoinduced electron transfer process from porphyrin units to GO, which acts as an electron acceptor. The surface plasmon coupling effect promoted by the AuNP@GO hybrids, proved to be effective only in the case of the noncovalent hybrid, detected through the decrease of the porphyrin fluorescence lifetime and increase in the emission intensity in solution, in good agreement with FLIM results on deposited samples.